2005
DOI: 10.4103/0019-5545.55944
|View full text |Cite
|
Sign up to set email alerts
|

Factitious schizophrenia

Abstract: Factitious disorder is a challenging phenomenon in clinical practice. An inconsistent clinical picture and the presence of symptoms that do not respond to the seemingly appropriate treatment should alert the clinician about the possibility of such a diagnosis. A case of factitious psychological symptoms suggestive of schizophrenia is reported, and the issues of diagnosis and management are discussed in the light of the available literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…After a thorough search in Medline, PubMed, Embase, Medknow databases, we came across a few case reports from India of varied presentations like factitious schizophrenia,[ 15 ] multiple physical and sexual complaints,[ 16 ] and oliguria,[ 17 ] whereas detailed case series and long-term studies are yet to be reported.…”
Section: Introductionmentioning
confidence: 99%
“…After a thorough search in Medline, PubMed, Embase, Medknow databases, we came across a few case reports from India of varied presentations like factitious schizophrenia,[ 15 ] multiple physical and sexual complaints,[ 16 ] and oliguria,[ 17 ] whereas detailed case series and long-term studies are yet to be reported.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge on the disposition and absorption characteristics of SRT in animals can help to interpret results in humans, such as drug-drug interactions [21,22] and side effects [23][24][25], and to establish relationships between plasma concentrations and pharmacodynamics [26,27]. Thus, the potential hepatotoxicity of SRT has been associated with mitochondrial dysfunction in rats [28], and a rat model of Huntington's disease has been used to study the protective effect of orally administered SRT against induced cognitive dysfunction [29,30]. Pharmacokinetic studies relating administered doses with plasma levels obtained in rats could improve the extrapolation of results to humans, relating the observed effects to the SRT plasma levels rather than to the administered doses.…”
mentioning
confidence: 99%
“…We are grateful to the authors of “factitious schizophrenia”[ 1 2 ] for having opened the Pandora's box again. A case report is to be presented on the basis of facts, logic and reason.…”
mentioning
confidence: 99%
“…There are certain fallacies inherent in their deductive and inductive reasoning. The patient's initial contact with the psychiatrist for depression, transient blindness (para 4, page 170)[ 1 ] and schizophrenia (para 6, page 169)[ 1 ] was at the age of 16 years. The diagnosis of schizophrenia was confirmed by the psychiatrist in the Department of Psychiatry, Pgimer0 (post graduate institute of medical education and research, Chandigarh), and treated for more than a year with antipsychotic drugs, i.e., Risperdone and Ziprasidone; whence, the patient developed left-sided gynecomastia.…”
mentioning
confidence: 99%
See 1 more Smart Citation